Interactions Between Ephedra sinica and Prunus armeniaca: From Stereoselectivity to Deamination as a Metabolic Detoxification Mechanism of Amygdalin - Qin, Yan; Wang, Shanshan; Wen, Qiuyu; Xia, Quan; Wang, Sheng; Chen, Guanjun; Sun, Jiayin; Shen, Chenlin; Song, Shuai (Frontiers in Pharmacology, 2021)
Mahuang-Xingren (MX, Ephedra sinica Stapf-Prunus armeniaca L.) is a classic herb pair used in traditional Chinese medicine. This combined preparation reduces the toxicity of Xingren through the stereoselective metabolism of its main active ingredient amygdalin. However, whether stereoselectivity is important in the pharmacokinetics properties of amygdalin either in the traditional decoction or in the dispensing granules is unclear. Amygdalin is hydrolyzed to metabolite, prunasin, which produces hydrogen cyanide by degradation of the cyanogroup. A comprehensive study of the metabolic pathway of amygdalin is essential to better understand the detoxification process. In this paper, potential detoxification pathway of MX was further discussed with regard to herb interactions. The pharmacokinetics parameters and metabolism of amygdalin and prunasin were investigated by comparing the traditional decoction and the dispensing granules preparations. In addition, several potential metabolites were characterized in an incubation system with rat liver microsome or gut microbial enzyme. The combination of Xingren with Mahuang reduces exposure to D-amygdalin in vivo and contributes to its detoxification, a process that can be further facilitated in the traditional decoction. From the in vitro co-incubation model, 15 metabolites were identified and classified into cyanogenesis and non-cyanogenesis metabolic pathways, and of these 10 metabolites are described for the first time. The level of detoxified metabolites in the MX traditional decoction was higher than in the dispensing granules. The metabolism of amygdalin by the gut microbial enzymes occurred more rapidly than by the rat liver microsome. These results indicated that combined boiling both herbs during the preparation of the traditional decoction preparation may induce several chemical changes that will influence drug metabolism in vivo. The gut microbiota may play a critical role in amygdalin metabolism. In conclusion, detoxification of MX may result 1) during the preparation of the decoction, in the boiling phase and 2) from the metabolic pathways activated in vivo. Stereoselective pharmacokinetics and deamination metabolism have been proposed as the detoxification pathway underlying the compatibility of MX. Metabolic detoxification of amygdalin was quite different between two combinations, which indicates that the MX decoctions should not be completely replaced by its dispensing granules.